Improving the Physical Properties of Nanofibers Prepared by Electrospinning from Polyvinyl Chloride and Polyacrylonitrile at Low Concentrations - Salih Abbas Habeeb; Baseem Ali Nadhim; Ban Jawad Kadhim; Mohammed Salam Ktab; Ali Jawad Kadhim; Farqad Saleem Murad (Advances in Polymer Technology)
In this study, both polyvinyl chloride (PVC) and polyacrylonitrile (PAN) were dissolved in dimethyl formaldehyde (DMF) with 8 wt. % concentrations at 25 : 75, 50 : 50, and 75 : 25 of PVC: PAN blending. For the investigation of the homogeneity and compatibility of mixture polymer solutions, it is examined by rheological properties such as viscosity, shear stress, shear rate, and calculation of the flow behavior index, while the investigation of the stability and high density of nanofibers without beads used field-emission scanning electron microscopy (FE-SEM), Fourier transform near-infrared spectroscopy (FT-NIR), X-ray diffraction (XRD), and differential scanning calorimetry-thermogravimetric analysis (DSC-TGA). The results show that blending of PAN with PVC leads to improving of the electro spun ability of PVC with more stability, and the mean nanofiber diameter was 90.873±40.82 nm at 25 : 75 PVC: PAN. Moreover, mechanical properties are ultimate tensile strength and modulus of elasticity decreasing with decreasing the blending ration from pure PVC to 75 : 25 PVC: PAN nanofibers by 71% and 83%, respectively, while the elongation at break increases by 79%, and decomposition temperatures decreased from 451.96 to 345.38°C when changing the PVC content from pure PVC to 25 : 75 PVC: PAN. On the other hand, changing of the nanofiber behavior from hydrophobicity to hydrophilic increased the PAN content in PVC: PAN blends. Furthermore, the low interaction between the chains of polymers and the crystallinity (%) and crystalline size (nm) of blend nanofibers slightly decreased compared to the pure polymers. According to all tests, the 25: 75 PVC: PAN was the best blending ratio, which gave a more stable nanofiber produced at low concentrations and more compatible between the PVC and PAN.